IMPLEMENTASI MANAJEMEN PENGELOLAAN KELAS PADA PROSES PEMBELAJARAN BAHASA INGGRIS DI PERGURUAN TINGGI UNIVERSITAS TEUKU UMAR - Rusma Setiyana; Endah Anisa Rahma (universitas teuku umar, 2018)
ABSTRACT The purpose of this study was to examine the implementation of classroom management in teaching learning process at Universitas of Teuku Umar Meulaboh Aceh Barat. The population of this sutdy was all students who have already taken English class either in the odd or in the even semester. Only was 10 % of the students obtained from Economics, Engineering, Agricultural, Social and Political Science, Fisheries and Marine Science, and Public Health Faculty randomly as the representative of the population. The instrument used to collect the data of this quantitative study was questionaire consisting of 10 closed questions. The data then was analyzed by using percentage with univariat method. The result shows that classroom management used by English lecturer at Universitas of Teuku Umar was very good averagely except about reward and social interaction among students. In detail, only 40% students agreed that the lecturer give them some reward and only 53,2% students agreed that they learned English language with their friends. Keyword: Classroom Management, English, Teaching Learning Process.